Eosinophilic Colitis: University of Minnesota Experience and Literature Review - Wolfgang B. Gaertner; Jennifer E. MacDonald; Mary R. Kwaan; Christopher Shepela; Robert Madoff; Jose Jessurun; Genevieve B. Melton (Gastroenterology Research and Practice)
Eosinophilic colitis is a rare form of primary eosinophilic gastrointestinal disease that is poorly understood. Neonates and young adults are more frequently affected. Clinical presentation is highly variable depending on the depth of inflammatory response (mucosal, transmural, or serosal). The pathophysiology of eosinophilic colitis is unclear but is suspected to be related to a hypersensitivity reaction given its correlation with other atopic disorders and clinical response to corticosteroid therapy. Diagnosis is that of exclusion and differential diagnoses are many because colonic tissue eosinophilia may occur with other colitides (parasitic, drug-induced, inflammatory bowel disease, and various connective tissue disorders). Similar to other eosinophilic gastrointestinal disorders, steroid-based therapy and diet modification achieve very good and durable responses. In this paper, we present our experience with this rare pathology. Five patients (3 pediatric and 2 adults) presented with diarrhea and hematochezia. Mean age at presentation was 26 years. Mean duration of symptoms before pathologic diagnosis was 8 months. Mean eosinophil count per patient was 31 per high-power field. The pediatric patients responded very well to dietary modifications, with no recurrences. The adult patients were treated with steroids and did not respond. Overall mean followup was 22 (range, 2–48) months.